2023
DOI: 10.1021/acsami.3c05064
|View full text |Cite
|
Sign up to set email alerts
|

Killing Bacteria by Faradaic Processes through Nano-Hydroxyapatite/MoOx Platforms

Abstract: Following the secular idea of ″restitutio ad integrum″, regeneration is the pursued option to restore bones lost after a disease; accordingly, complementing antibiotic and regeneration capacity to bone grafts represents a great scientific success. This study is a framework proposal for understanding the antimicrobial effect of biocompatible nano-hydroxyapatite/MoO x (nano-HA/MoO x ) platforms on the basis of their electroactive behavior. Through cyclic voltammetry and chronoamperometry measurements, the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Abnormal osteoclast activation is one of the major causes of bone repair failure. [ 242 ] It has been reported that the exposure of osteoclasts to ES results in voltage‐gated Ca 2+ channels mediating the influx of Ca 2+ ions, leading to the disruption of actin ring formation and subsequent alterations in the cell cytoskeleton, ultimately impeding the formation of osteoclast podosomes (specific adhesive structures), and, in turn, inhibiting the bone‐resorbing activity of these cells. [ 243 ] The application of electroactive biomaterials to inhibit osteoclast activation and promote bone tissue repair could be a feasible strategy.…”
Section: Application Of Electroactive Biomaterials In Bone Tissue Reg...mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal osteoclast activation is one of the major causes of bone repair failure. [ 242 ] It has been reported that the exposure of osteoclasts to ES results in voltage‐gated Ca 2+ channels mediating the influx of Ca 2+ ions, leading to the disruption of actin ring formation and subsequent alterations in the cell cytoskeleton, ultimately impeding the formation of osteoclast podosomes (specific adhesive structures), and, in turn, inhibiting the bone‐resorbing activity of these cells. [ 243 ] The application of electroactive biomaterials to inhibit osteoclast activation and promote bone tissue repair could be a feasible strategy.…”
Section: Application Of Electroactive Biomaterials In Bone Tissue Reg...mentioning
confidence: 99%
“…In another study, Sieben et al. [ 242 ] designed an electroactive biomaterial based on nano‐HAp and MoOx, which was observed to mediate extracellular electron transfer, altering the function of bacterial cell membranes and accelerating the death of pathogens. Furthermore, hydroxyapatite demonstrated favorable biocompatibility, mechanical characteristics, and osteoinductive properties, thereby further enhancing bone tissue regeneration.…”
Section: Application Of Electroactive Biomaterials In Bone Tissue Reg...mentioning
confidence: 99%